PENDAMPINGAN BERBASIS COLLABORATIVE LEARNING UNTUK PENINGKATAN KETERAMPILAN REFLEKSI KRITIS GURU-GURU DI GUGUS 5 KECAMATAN BOAWAE - Wilibaldus Bhoke; Melkior Wewe; Maria Carmelita Tali Wangge; Katarina Kedhi (Universitas Mataram, 2023)
A teacher's use of suitable methods is one way to ensure that a unit of instruction runs smoothly and students learn as intended. In other words, we should always reflect on our learning processes to identify where we went wrong and how to fix it. This way, we can make sure that our methods are effective. When it comes to collaborative learning, the teacher's stance should center on two things: modeling the necessary behaviors for effective collaboration and coming up with clear objectives for the class to work toward. The purpose of this study was to examine whether or not teachers in cluster 5 of the Boawae District were able to enhance their critical reflection skills through collaborative learning-based mentoring after taking part in all classroom activities. A qualitative descriptive method based on a case study approach was employed in this research. This study's data came from a combination of observation and joint discussion. Six educators from six different schools in cluster 5 of the Boawae District participated as subjects. Concerning teachers' ability to reflect on their own teaching practices, an issue has been brought up. Educators can discover answers or ways out of these problems by critically reflecting on themselves in light of these issues. Teachers' ability to critically reflect on their own practice improved after using collaborative learning strategies, according to this study. Teachers' ability to guide students through the learning process can be enhanced through the implementation of this collaborative learning strategy. The average percentage of results achieved by teachers after engaging in this mentoring activity is 70,0%, which proves it. The ability to effectively apply knowledge is exhibited by these educators. Educators that are adept at critical reflection can study their students' learning processes and use that knowledge to inform their own pedagogical decisions. Teachers' pedagogical choices have a significant impact on their students' achievement. As a result, 70,0% more teachers in Boawae District are now engaging in critical reflection thanks to mentoring activities based on Collaborative Learning.